2020
DOI: 10.1523/jneurosci.2121-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of AMPA and NMDA Receptors to Persistent Firing in the Dorsolateral Prefrontal Cortex in Working Memory

Abstract: Many tasks demand that information is kept online for a few seconds before it is used to guide behavior. The information is kept in working memory as the persistent firing of neurons encoding the memorized information. The neural mechanisms responsible for persistent activity are not yet well understood. Theories attribute an important role to ionotropic glutamate receptors, and it has been suggested that NMDARs are particularly important for persistent firing because they exhibit long time constants. Ionotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 76 publications
1
24
1
Order By: Relevance
“…Our findings support the concept that long-term motor skill training is associated with a complex bihemispheric cortical-subcortical network [2,18]. The brain areas identified in this study are functionally related to motor control (i.e., PrG) [19,20], interpretation of sensory information (i.e., IPL) [21][22][23], body image (i.e., IPL) [21,22], spatial perception (i.e., IPL and MTG) [23,24], spatial attention (i.e., IPL) [21][22][23], vision (i.e., IPL and MTG) [21][22][23][24], executive function (i.e., RMFG and IPL) [22,[25][26][27], and working memory (i.e., RMFG and SFG) [25][26][27][28]. A unique feature of gymnastics events is that each requires acrobatic performances comprising speed, strength, and flexibility; these physiological functions are all critical to supporting elaborate body movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings support the concept that long-term motor skill training is associated with a complex bihemispheric cortical-subcortical network [2,18]. The brain areas identified in this study are functionally related to motor control (i.e., PrG) [19,20], interpretation of sensory information (i.e., IPL) [21][22][23], body image (i.e., IPL) [21,22], spatial perception (i.e., IPL and MTG) [23,24], spatial attention (i.e., IPL) [21][22][23], vision (i.e., IPL and MTG) [21][22][23][24], executive function (i.e., RMFG and IPL) [22,[25][26][27], and working memory (i.e., RMFG and SFG) [25][26][27][28]. A unique feature of gymnastics events is that each requires acrobatic performances comprising speed, strength, and flexibility; these physiological functions are all critical to supporting elaborate body movements.…”
Section: Discussionmentioning
confidence: 99%
“…The IPL is known to be involved in various neural functions, including spatial attention, multimodal sensory integration, body image, oculomotor control, and hand-eye coordination [21][22][23]. The RMFG is critical for executive function and working memory [25][26][27]. Working memory is a series of memory operations that involve manipulating and utilizing information while temporarily retaining it in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical accounts posit that NMDA-mediated recurrent excitation coupled with fast inhibition (Chaudhuri et al, 2015;Wang, 1999Wang, , 2008, as well as cell-intrinsic properties (Duarte and Morrison, 2019;Gjorgjieva et al, 2016;Koch et al, 1996), are crucial for shaping neuronal timescales. While in vitro and in vivo studies in model organisms (van Vugt et al, 2020;Wang et al, 2013) can test these hypotheses at the single-neuron level, causal manipulation and large-scale recording of neuronal networks embedded in the human brain is severely limited. Here, we apply an approach analogous to multimodal single-cell profiling (Bomkamp et al, 2019) and examine the transcriptomic basis of neuronal dynamics at the macroscale.…”
Section: Fig 2 Timescale Increases Along the Anatomical Hierarchy Imentioning
confidence: 99%
“…In this regard, a recent study by (Woodcock et al 2018) showed that glutamate levels rise in the human dlPFC in response to increased WM demand. On the other hand, inhibiting glutamate release via local administration of mGlu2/3 (auto)receptor agonists, or blockade of the postsynaptic ionotropic glutamate receptors disrupted sustained firing of local pyramidal neurons and impaired WM performance in animals (Gregory et al 2003;van Vugt et al 2020;Wang et al 2013). Recent studies by our laboratory and others, showed that systemic or local intra-PrL inhibition of mGlu5 receptors impairs DMS task performance Hámor et al 2020;Hernandez et al 2018).…”
Section: Discussionmentioning
confidence: 98%